The value of air conditioning - Phelan, P. E.; Phelan, B. E.; Sharma, A. (Frontiers in Energy Efficiency, 2024)
The advent of global climate change and rising incomes, particularly in some developing countries such as Egypt, means that the use of air conditioning is poised for a dramatic increase over the next few decades. Although this anticipated increase appears inevitable, it is often associated with a negative connotation because of the increased energy demands and greenhouse gas emissions associated with expanded air conditioning use. Yet, the benefits of air conditioning are not often described in existing literature in conjunction with its associated negative externalities. For example, higher productivity in commercial buildings, and positive health benefits in all manner of buildings (residential, commercial, and industrial) could potentially offset the greater energy consumption and related disadvantages. A levelized cost of cooling (LCOC) analysis is presented to quantify under what circumstances building air conditioning provides benefits that exceed its costs, and vice versa. The LCOC is calculated for the application of air conditioning to a small office building located in either Phoenix, Arizona, United States, or in Cairo, Egypt. The electrical energy required for cooling is calculated with EnergyPlus software. The results indicate that the benefits of air conditioning far outweigh its disadvantages for the Phoenix location, largely because of the productivity benefits derived from maintaining the interior temperature at a comfortable setting. The results for Egypt are more nuanced, but still indicate the overall benefits of air conditioning in an office environment.